Neural Pruning Search for Real-Time Object Detection of Autonomous Vehicles - Zhao, Pu; Yuan, Geng; Cai, Yuxuan; Niu, Wei; Liu, Qi; Wen, Wujie; Ren, Bin; Wang, Yanzhi; Lin, Xue (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
Object detection plays an important role in self-driving cars for security development. However, mobile systems on self-driving cars with limited computation resources lead to difficulties for object detection. To facilitate this, we propose a compiler-aware neural pruning search framework to achieve high-speed inference on autonomous vehicles for 2D and 3D object detection. The framework automatically searches the pruning scheme and rate for each layer to find a best-suited pruning for optimizing detection accuracy and speed performance under compiler optimization. Our experiments demonstrate that for the first time, the proposed method achieves (close-to) real-time, 55ms and 97ms inference times for YOLOv4 based 2D object detection and PointPillars based 3D detection, respectively, on an off-the-shelf mobile phone with minor (or no) accuracy loss.